4x+6-2x=2(x-3)

Simple and best practice solution for 4x+6-2x=2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+6-2x=2(x-3) equation:


Simplifying
4x + 6 + -2x = 2(x + -3)

Reorder the terms:
6 + 4x + -2x = 2(x + -3)

Combine like terms: 4x + -2x = 2x
6 + 2x = 2(x + -3)

Reorder the terms:
6 + 2x = 2(-3 + x)
6 + 2x = (-3 * 2 + x * 2)
6 + 2x = (-6 + 2x)

Add '-2x' to each side of the equation.
6 + 2x + -2x = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + 0 = -6 + 2x + -2x
6 = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 = -6 + 0
6 = -6

Solving
6 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4x^2-12x-10=0 | | x(x+4)=-84 | | 7x^2-36x+6=0 | | 3x(x-1)+15=7 | | 40+2y-16=11y-11-4y | | 1223423123x=213123123 | | -3x+18=-10x+4 | | 3x+9=5x-19 | | 6(2.5)+3y=12 | | (3x)(3x-2)(x)=540 | | 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 | | 4x-7=36 | | x^3-5x^2+4x-2=0 | | 42x=35x+70 | | 6(4n-4)=-60 | | 8-2n=40 | | 7x+7=-5x+43 | | 49s^2-14s+1=0 | | 8k^2-20=-9k | | 5(7+2)=x-11 |

Equations solver categories